A case of NASH with genetic predisposition successfully treated with an SGLT2 inhibitor: a possible involvement of mitochondrial dysfunction. (24th December 2022) - Nakajima, Rikako; Sekiya, Motohiro; Furuta, Yasuhisa; Miyamoto, Takafumi; Sato, Masashi; Fukuda, Kuniaki; Hattori, Keiichiro; Suehara, Yasuhito; Sakata-Yanagimoto, Mamiko; Chiba, Shigeru; Okajima, Yuka; Matsuzaka, Takashi; et al.
Abstract : Summary: In this study, we herein describe a 47-year-old Japanese woman who manifested inheritable non-alcoholic steatohepatitis (NASH) and severe dyslipidemia. Interestingly, her NASH progression was ameliorated by treatment with a sodium–glucose co-transporter 2 (SGLT2) inhibitor. This inheritability prompted us to comprehensively decode her genomic information using whole-exome sequencing. We found the well-established I148M mutation in PNPLA3 as well as mutations in LGALS3 and PEMT for her NASH. Mutations in GCKR may contribute to both NASH and dyslipidemia. We further mined gene mutations potentially responsible for her manifestations that led to the identification of a novel M188fs mutation in MUL1 that may be causally associated with her mitochondrial dysfunction. Our case may provide some clues to better understand this spectrum of disease as well as the rationale for selecting medications. Learning points: While the PNPLA3 I148M mutation is well-established, accumulation of other mutations may accelerate susceptibility to non-alcoholic steatohepatitis (NASH). NASH and dyslipidemia may be intertwined biochemically and genetically through several key genes. SGLT2 inhibitors emerge as promising treatment for NASH albeit with interindividual variation in efficacy. Genetic background may explain the mechanisms behind the variation. A novel dysfunctional mutation in MUL1 may lead to metabolic inflexibilities through impaired mitochondrial dynamics and function.